100 greatest sports champions (Danbury, CT : Grolier Educational, 1997)
Examines notable athletes in such sports as baseball, cycling, and tennis
Includes index
Keywords: Athletes -- Biography -- Juvenile literature; Athletes -- Rating of -- Juvenile literature; Athletes